Diabetic foot plantar pressure monitoring system using force sensitive resistor system - Nur Suhaila, Nur Suhaila; Huong, Audrey (Penerbit Uthm, 2019)
Many people are suffering from diabetes; it was the major cause that has led many to hospitalization. According to [1], patients with Type 2 diabetes suffering from peripheral neuropathy are at high risks of developing diabetic foot syndrome, which leads to foot ulcerations that caused mainly by high peak plantar pressures. Without early prevention and intervention [2], diabetic foot ulcer has 15 times greater risk to cause lower limb amputation. Therefore, further studies on early prevention may help in healthcare management.